PENGARUH STRATEGI TARIF DAN PROMOSI HOTEL TERHADAP KEPUTUSAN MENGINAP WISATAWAN NUSANTARA PADA HOTEL MELATI DI GILI TRAWANGAN - Budiastuti, Dende Dewi Tresni (Jurnal Magister Manajemen, 2016)
The objective of the study was to evaluate the influence of strategic price and hotel promotions toward consumer decision to stay in non-star hotel. Associative research design was adopted as the study guide. Purposive sampling techniques were used in which 100 copies of the research instrument were administered to domestic tourists which stayed for two or more days in non-star hotels, Gili Trawangan, out of which 100 copies of questionnaire were filled and returned. Pearson Product Moment correlation was used to analyse the data generated from respondents. The findings revealed that strategic price and hotel promotions have significant influence on consumer decision at 0,05 level (2-tailed). The result of the research shows both of the variables significantly affecting consumer decision. Furthermore, hotel promotions ranks the first follow by strategic price. This research will help the management of hotel to understand and recognize the ranking of variables affecting consumer decision of domestic tourists to stay in non-star hotel. Keywords: Hospitality, Strategic Price, Promotion, Decision to Stay, Domestic Tourist, and Gili Trawangan.